SOCIAL-PSYCHOLOGICAL ASPECTS OF THE FORMATION OF ENTERPRISE CHARACTERISTICS OF PRE-SCHOOL CHILDREN (TAMADDUN NURI JURNALI, 2024)
This article examines the social psychological aspects of the formation of initiative in preschool children. We discuss the role of family environment and educational environment in shaping these important children’s initiative traits.